Local Government Prayers in Australia - Beck, Luke (Journal for the academic study of religion, 2023)
Many local governments in Australia open their council meetings with prayer and have done so for some time. Yet this phenomenon has been largely ignored by the literature examining religion-government interactions in Australia. After outlining the origins of local government prayers, this article goes on to show that approximately one-third of Australian local governments have a prayer practice (rising to more than half of local governments in New South Wales and Victoria), that almost all of those prayer practices are exclusively Christian, and that in some states communities with the smallest Christian populations are more likely to have a council with a prayer practice than communities with the largest Christian populations. This phenomenon does not sit neatly with existing accounts of post-secularism in Australia. The article suggests that local government prayers in Australia also pose a challenge to existing post-secular explanatory accounts of the nature of religion-government interactions in Australia and speak to the need to develop more nuanced accounts that distinguish between the policy realm and institutional issues in developing accounts of the relationship between religion and government in Australia.